Research Funding in Polish Higher Education – Moving on to Highly Competitive System - Barbara GRABINSKA (Communications of International Proceedings, 2020)
Research funding plays a key role in directing the development of science and stimulating the research productivity, which is crucial in today’s economy based on knowledge. Around the world, we can observe the growing dissemination of the model of research financing based on the composition of competitive grant funding for individual researchers and performance-based funding for subsidizing institutions of higher education.  Poland has transformed in a relatively short period of time from a system of block-based research funding to highly competitive model of research financing, where substantial amount of total research resources is allocated for project funding and institutional financing is based on performance metrics. The aim of the study is to present the evolution in the structure of revenues for research activity of public higher education institutions (HEI) in Poland with the focus on project financing distributed by two research agencies: National Science Center - responsible for basic research and National Centre for Research and Development -  responsible for supporting applied and experimental research. The study is based on the data from the financial statements of public HEI over the period 2011 – 2018. Conclusions are vital for the evidence-based policy regarding research funding.
Keywords: Higher Education; System of Public Research Financing; Project Funding; Poland.